KEDUDUKAN PERATURAN DESA DALAM SISTEM PEMBENTUKAN PERATURAN PERUNDANG UNDANGAN NASIONAL - Kadek Wijayato; Lusiana Margareth Tijow; Fence M. Wantu (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2020)
ABSTRACTThe purpose of this study is to Analyze the position of Village Regulations after the enactment of Law Number 12 of 2011 concerning the Formation of Legislation and Know and Analyze the Urgency of Village Regulations in the Implementation of Village Government Affairs. The study uses a type of normative juridical legal research using the approach to the Act (Statute Approach), and Conceptual Approach (Conceptual Approach). The results of this study indicate: First, That the Position of the Village Regulation Post the Law No. 12 of 2011 is legally normative is not explicitly recognized in Law No. 12 of 2011 although the previous law still recognizes this point clearly in Law Number 10 of 2004 Village regulations state that Article 7 paragraph (2) letter c states "Village regulations / equivalent regulations, made by village representative bodies or other names together with village heads or other names." However, with the change from Law No. 10 to Law No. 12 In 2011, it is clear that Article 7 only mentions the type and hierarchy of laws only to Regional Regulations. Second, That the Urgency of Village Regulations in the Implementation of the Government Administration Desadalam in its development to carry out government functions in the village. The governmental function is derived from co-administration tasks originating from a higher level of government, namely regency / city. Law Number 6 of 2014 concerning Villages provides space for villages and village apparatus to be creative and has a legal basis in terms of improving village welfare, as we know that the village is the lowest unit of state administration in Indonesia.Keywords: Position of Village Regulation; Village Government. Village Autonomy.